Confirmatory Factor Analysis: Faktor-Faktor Penentu Agribisnis Mangga Di Kabupaten Majalengka Berdasarkan Penguasaan Lahannya - Rasmikayati, Elly; Saefudin, Bobby Rachmat (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Mango farmers in Majalengka Regency who have narrow land tenure tend to market their mangrove production only to traditional markets. Even if they are able to improve their agribusiness behavior, even smallholder farmers should have the opportunity to market mango production to the modern market which includes supermarkets and exports that will increase farmers income. The purpose of this paper are: 1) To analyze the characteristics of mango farmers in Majalengka Regency; and 2) Analyzing the determinants of mango agribusiness in Majalengka Regency based on their land tenure. The research method used survey techniques in Majalengka District as one of the centers of mango production in West Java. The sample of farmers determined using 130 stratification sampling techniques. Data analysis techniques carried out using descriptive statistical analysis, and confirmatory factor analysis. The results of the study show that the proportion of farmers with narrow land tenure is 43 people (33.08%) while 87 people (66.92%) are mango farmers who are cultivating medium and wide land. Farmers who have narrow land tenure have a more homogeneous age than farmers whose land area is medium and wide, but more heterogeneous in terms of mango farming experience. The level of education of farmers with narrow land is lower than that of farmers whose land area is medium and wide. Factors that determine mango agribusiness in Majalengka Regency for farmers with narrow mastery, all significant factors are social factors, economic factors, technological factors, resource factors, institutional factors and cultural factors. Whereas for farmers with medium and broad mastery, significant factors are social factors, technological factors, resource factors and institutional factors, while economic factors and cultural factors are not significant.